Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1155/2020/2314693
|View full text |Cite
|
Sign up to set email alerts
|

Role of 17β-Estradiol on Cell Proliferation and Mitochondrial Fitness in Glioblastoma Cells

Abstract: Gliomas are the most common primary tumors of the central nervous system (CNS) in the adult. Previous data showed that estrogen affects cancer cells, but its effect is cell-type-dependent and controversial. The present study aimed to analyze the effects of estradiol (E2, 5 nM) in human glioblastoma multiforme U87-MG cells and how it may impact on cell proliferation and mitochondrial fitness. We monitored cell proliferation by xCELLigence technology and mitochondrial fitness by assessing the expression of genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 47 publications
(51 reference statements)
3
14
0
Order By: Relevance
“…Once we demonstrated that E2 induces cell growth in GBM cells, we decided to investigate the relationship between E2 and canonical cellular processes of EMT activation, such as morphological and actin cytoskeleton organization changes, EMT marker expression, as well as cellular migration and invasion, which represent the main functional consequences of cells that undergo EMT. Additionally, it is worth mentioning that recently Castruccio et al demonstrated that E2 significantly increases cell proliferation in U87 cells [ 92 ], which is consistent with our previously published results [ 45 ]. Still, our survival analysis showed that both ER-α and ER-β expression was positively correlated with a poor prognosis.…”
Section: Discussionsupporting
confidence: 92%
“…Once we demonstrated that E2 induces cell growth in GBM cells, we decided to investigate the relationship between E2 and canonical cellular processes of EMT activation, such as morphological and actin cytoskeleton organization changes, EMT marker expression, as well as cellular migration and invasion, which represent the main functional consequences of cells that undergo EMT. Additionally, it is worth mentioning that recently Castruccio et al demonstrated that E2 significantly increases cell proliferation in U87 cells [ 92 ], which is consistent with our previously published results [ 45 ]. Still, our survival analysis showed that both ER-α and ER-β expression was positively correlated with a poor prognosis.…”
Section: Discussionsupporting
confidence: 92%
“…Based on our present findings, we formulated the idea that the inhibitory effect of LOS on the EMT process in GBM cells may also be indirectly reinforced by its inhibitory action on local estrogen production [ 45 , 46 ]. Indeed, estradiol not only stimulates glioblastoma cell proliferation well-fitting with our present data [ 47 ] but also induces a change in cell morphology displaying an elongated cell phenotype correlated with actin filaments rearrangements, together with an increase of cell migration, invasion, and upregulation of EMT markers such as Vimentin and N-Cadherin in GBM cell lines [ 47 , 48 , 49 , 50 ].…”
Section: Discussionsupporting
confidence: 85%
“…At low concentrations, estradiol increased proliferation and mitochondrial fitness of U87 cells. [ 44 ] Estradiol increased migration of T98G GBM cells and increased cell invasion in U87 GBM cells, in a concentration dependent manner ranging from low to high concentrations. [ 45 ] In another study, estradiol increased migration of C6 cells but not in F98 cells, both of which are rat GBM cell lines.…”
Section: Role Of Estrogen In Gliomamentioning
confidence: 99%